AKULTURASI ISLAM DAN BUDAYA LOKAL PADA MASYARAKAT AGRARIS (Pengalaman Petani Klutuk di Kabupaten Indramayu) - Khaerul Umam (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2022)
Religion that preached by means of persuasive with acculturation patterns, more easily accepted. And it create a new color in the existing cultural traditions. Klutuk farmers with all the ritual tradition is entrenched, able to accept the arrival of a new religion due to the new value that does not exclude and offend them as people who have been cultured before. Hinduism and Buddhism that come later, patterned religion earth, existence is able to maintain and further strengthen that tradition. Until Islam came, although he patterned sky religion whose mission is to spread (da’wah) teachings, but do not lead to confl ict with the tradition of the klutuk farmers. The result, in addition to reinforce, is also able to fi ll the spiritual void by providing transcendent value and a new outlook on the tradition. So, appear the traditions that shape, still relatively like the old one, but it has a value of renewal.